O-4 CLINICAL, HISTOLOGICAL AND SEROLOGICAL FEATURES OF AUTOIMMUNE-LIKE ACUTE LIVER INJURY AFTER SARS-COV-2 VACCINATION - Marlene Padilla Lopez; Natalia Sobenko; Lucrecia Garcia Olivera; Agustina Martinez Garmendia; Eduardo Mullen; Paola Casciato; Sebastian Marciano; Alejandra Villamil (Annals of Hepatology, 2023)
Introduction and Objectives: Acute autoimmune-like liver injury has been increasingly reported after vaccination against SARS-CoV-2. Pathogenesis, steroid requirement and long-term prognosis are unknown. This study aimed to evaluate clinical, serological and histological features, response to treatment and prognosis in patients with post-vaccination acute hepatitis. Materials and Methods: We included patients without known pre-existing liver diseases with transaminase levels ≥ 2.5 upper limits of normal within 90 days after the SARS-CoV-2 vaccine with an available liver biopsy. Clinical data and outcomes after a six months follow-up were collected. Results: 17 patients were included,12 females, median age 60 (51,5/66) exposed to vectorial (Sputnik V n=7, AstraZeneca n=6), inactivated (Sinopharm n=3) or ARNm Vaccines (Moderna=1). In 8 patients, liver injury developed after the first dose and in 7 after the second dose and in 2 after the third dose. The median time to the development of injury was 33(23,50/53,50) days. Eight patients had a history of extrahepatic autoimmune disease and five patients had metabolic syndrome and used statins. Immune serology showed anti-antinuclear antibody in 10 (58,8%), anti-smooth muscle antibody in 5(29,4%). 14/17 patients presented with elevated IgG levels. Liver histology showed lobular hepatitis in 13/17, portal hepatitis in 17/17 with plasmocytic lymphocytic infiltrate and 4/17 had eosinophils, 6/17 with severe interface hepatitis, and one patient had fibrosis Ishak stage ≥3. 12/17 (70,5%) were treated with steroids. Transaminases improved in 17 cases and normalized in 6/12 by month 6. Only 1/17 developed liver function deterioration, yet no patient required liver transplantation. Most patients tolerated the tapering of steroids and in 6 azathioprine was started before month 3. Conclusions: Long-term follow-up might help to differentiate between induced classical autoimmune hepatitis, autoinflammatory self-limited events, or drug-induced liver injury in these patients.